Stress induced risk-aversion is reverted by D2/D3 agonist in the rat - Morgado, P.; Marques, F.; Ribeiro, B.; Leite-Almeida, H; Pêgo, J M; Rodrigues, A. J.; Dalla, C; Kokras, N; Sousa, N.; Cerqueira, J. J. (Eur Neuropsychopharmacol, 2015)
Stress exposure triggers cognitive and behavioral impairments that influence decision-making processes. Decisions under a context of uncertainty require complex reward-prediction processes that are known to be mediated by the mesocorticolimbic dopamine (DA) system in brain areas sensitive to the deleterious effects of chronic stress, in particular the orbitofrontal cortex (OFC). Using a decision-making task, we show that chronic stress biases risk-based decision-making to safer behaviors. This decision-making pattern is associated with an increased activation of the lateral part of the OFC and with morphological changes in pyramidal neurons specifically recruited by this task. Additionally, stress exposure induces a hypodopaminergic status accompanied by increased mRNA levels of the dopamine receptor type 2 (Drd2) in the OFC; importantly, treatment with a D2/D3 agonist quinpirole reverts the shift to safer behaviors induced by stress on risky decision-making. These results suggest that the brain mechanisms related to risk-based decision-making are altered after chronic stress, but can be modulated by manipulation of dopaminergic transmission.
Keywords: *Risk-Taking; Animals; Chronic Disease; Decision Making/drug effects/*physiology; Decision-making; Disease Models, Animal; Dopamine; Dopamine Agonists/pharmacology; Dopamine/metabolism; Insula; Male; Orbitofrontal; Prefrontal Cortex/drug effects/*metabolism/pathology; Pyramidal Cells/drug effects/metabolism/pathology; Quinpirole; Quinpirole/pharmacology; Rats, Wistar; Receptors, Dopamine D2/agonists/*metabolism; Receptors, Dopamine D3/agonists/*metabolism; RNA, Messenger; stress; Stress, Psychological/drug therapy/*metabolism/pathology; uncertainty